2004
DOI: 10.2337/diabetes.53.5.1360
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Structure and Genotype-Phenotype Correlations of the Sulfonylurea Receptor and the Islet ATP-Sensitive Potassium Channel Gene Region

Abstract: The genes for the sulfonylurea receptor (SUR1; encoded by ABCC8) and its associated islet ATP-sensitive potassium channel (Kir6.2; encoded by KCNJ11) are adjacent to one another on human chromosome 11. Multiple studies have reported association of the E23K variant of Kir6.2 with risk of type 2 diabetes. Whether and how E23K itself-or other variant(s) in either of these two closely linked genes-influences type 2 diabetes remains to be fully determined. To better understand genotype-phenotype correlation at this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
216
4
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(238 citation statements)
references
References 43 publications
17
216
4
1
Order By: Relevance
“…A Pearson w 2 goodness-of-fit test to assess the level of genetic heterogeneity among sample populations was applied to both the study's data and data used in the pooled analyses as described previously. 62 …”
Section: Pooled Analysismentioning
confidence: 99%
“…A Pearson w 2 goodness-of-fit test to assess the level of genetic heterogeneity among sample populations was applied to both the study's data and data used in the pooled analyses as described previously. 62 …”
Section: Pooled Analysismentioning
confidence: 99%
“…In addition, we and others have demonstrated that gestational diabetes mellitus shares some genetic risk factors with type 2 diabetes [2]. For example, potassium inwardly rectifying channel subfamily J, member 11 (KCNJ11 E23K), glucokinase (GCK −30G>A) and transcription factor 1, hepatic; LF-B1, hepatic nuclear factor (HNF1), albumin proximal factor (TCF1, also known as hepatocyte nuclear factor 1-α [HNF1A I27L]) polymorphisms, all of which have been associated with type 2 diabetes [7][8][9], also increase the risk of gestational diabetes mellitus with a modest effect size [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, still lacking is knowledge on whether patients with LADA have the same frequency of the few type 2 diabetes susceptibility genes that have reproducibly been associated with type 2 diabetes, e.g. the Pro12Ala single-nucleotide polymorphism in PPARG, the E23K SNP in KCNJ11, or the recently described polymorphisms in TCF7L2 [13][14][15].…”
mentioning
confidence: 99%